Introduction to public health : promises and practices - Goldsteen, Raymond L. (Springer Publishing Company, 2015)
The only public health text to incorporate new Affordable Care Act legislation. Praise for the first edition:. ""More than just another preliminary textbook, this comprehensive introduction for those who are new to the field of public health weaves together its values, goals, and practices into a lucid introductory text.""--Sally Guttmacher, PhD. Professor, Director, Master's in Community Public Health Program. New York University. This second edition of Introduction to Public Health is the only text to encompass the new legislation implemented by the Affordable Care Act, with its focus on page